Role of Clathrin light chains in regulating invadopodia formation - Mukenhirn, Markus; Muraca, Francesco; Bucher, Delia; Asberger, Edgar; Cappio Barazzone, Elisa; Cavalcanti-Adam, Elisabetta A.; Boulant, Steeve (Cells, 2021)
One of the most fundamental processes of the cell is the uptake of molecules from the surrounding environment. Clathrin-mediated endocytosis (CME) is the best-described uptake pathway and regulates nutrient uptake, protein and lipid turnover at the plasma membrane (PM), cell signaling, cell motility and cell polarity. The main protein in CME is clathrin, which assembles as a triskelion-looking building block made of three clathrin heavy chains and three clathrin light chains. Compared to clathrin heavy chains (CHCs), the role of the two isoforms of clathrin light chains (CLCA and CLCB) is poorly understood. Here, we confirm that the simultaneous deletion of both CLCA/B causes abnormal actin structures at the ventral PM and we describe them, for the first time, as functional invadopodia rather than disorganized actin-cytoskeleton assembly sites. Their identification is based on the occurrence of common invadopodia markers as well as functional invadopodia activity characterized by an increased local proteolytic activity of the extracellular matrix proteins. We demonstrate that CLCA/B deletion impacts the intracellular trafficking and recovery of the matrix metalloproteinase 14 (MMP14) leading to its accumulation at the plasma membrane and induction of invadopodia formation. Importantly, we show that invadopodia formation can be prevented by depletion of MMP14. As such, we propose that CLCA/B regulate invadopodia formation by regulating MMP14 delivery to the plasma membrane.
Gesehen am 01.04.2021